2008
DOI: 10.1007/s12149-007-0159-z
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG-PET/CT as an indicator for resection of pulmonary epithelioid hemangioendothelioma

Abstract: A 60-year-old man with a 7-year history of multiple pulmonary nodules presented to our hospital because the nodules were seen to have increased in size on review of films on a regular medical checkup 1 week earlier. Computed tomography (CT) revealed multiple pulmonary nodules with calcification in the lungs. The largest nodule measuring 2.5 cm in the maximum dimension was lobulated and ill-defined. The patient underwent 18F-fluorodeoxyglucose positron emission tomography/CT (18F-FDG-PET/CT) to evaluate the mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
0
20
1
1
Order By: Relevance
“…[2022] Indeed, most patients who underwent PET/CT in our study showed increased FDG uptake at the corresponding lung lesions on CT. There was a trend of a wider range of SUVmax in the multinodular pattern, compared with relatively higher SUVmax in diffuse pleural and nodule/mass with pleural pattern.…”
Section: Discussionmentioning
confidence: 93%
“…[2022] Indeed, most patients who underwent PET/CT in our study showed increased FDG uptake at the corresponding lung lesions on CT. There was a trend of a wider range of SUVmax in the multinodular pattern, compared with relatively higher SUVmax in diffuse pleural and nodule/mass with pleural pattern.…”
Section: Discussionmentioning
confidence: 93%
“…18 F-FDG-PET/CT was recently reported by Watanabe et al as a useful diagnostic tool for indicating the suitability of resection for PEH. 3 They presented a case of PEH with two foci (one was 2.5 cm diameter; the size of other was not described), both of which had increased 18 F-FDG uptake. The fi rst case of PEH with 18 F-FDG positive was reported by Fagen et al However, the detailed clinical characteristics were not documented except that it measured 2 × 1 cm.…”
Section: Discussionmentioning
confidence: 99%
“…However, 18 F-fl uorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG-PET/ CT) was recently reported as a useful diagnostic tool. 3 We describe herein two cases of PEH, including the results of 18 F-FDG-PET/CT, and discuss them along with a review of the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…When SUV is high on FDG-PET, it is important for the lesion to be differentiated from a malignant tumor. However, some reports have shown that SUV is high even in benign tumors such as granulomas and inflammatory lesions [6][7][8][9]. In malignant tumors, SUVmax tends to be higher when the tumor grade is higher [10,11].…”
Section: Discussionmentioning
confidence: 99%